Answer:
If we have two quantities x and y, an inverse variation can be written as:
y = k/x
where k is a constant.
Now, we know that for this particular inverse variation the point (3, -4) is included.
Then we can find the value of k by replacing the values of the point in the general equation:
-4 = k/3
k = -4*3 = -12
Then our inverse variation is:
y = -12/x.
Then if we want another point that also does belong in the inverse variation, we can give x a different value and solve the equation for y.
For example, if x = 1
y = -12/1 = -12
then the point (1, -12) also does belong in the inverse variation.
if x = 6
y = -12/6 = -2
the point (6, -2) also does belong to the inverse variation